THE UNDERLYING PATTERNS OF CAFÉ TALK - ninuk krismanti (Jurnal Lingua Idea, 2016)
Café talk represents casual conversation that is usually taken for granted by people. This study is intended to reveal patterns of exchange structures underlying café talk. To achieve the objective of the study, the writer applies Francis and Hunston’s model of analysis (1992). Participatory observation is the technique used to collect the data. The method of analysis used in this study is referential method. Based on the analysis, it is found that there are 21 patterns constructing 1459 exchanges found in the data. Of the 1459 exchanges, 10 exchanges are found in organizational exchange category, and 1449 exchanges are found in conversational exchange category. Inform exchange, elicit exchange, and bound-elicit clarify exchange from conversational exchange category are the most prominent exchanges found in the data.